Arupakirinātar : varalāṟum nūlārāycciyum - Ceṅkalvarāya Piḷḷai, Va. Cu., 1883-1971 (SAMP early 20th-century Indian books project ;, 1947)
On the life and works of Aurṇakirinātar, 15th century Tamil poet.